Biofilm formation on polyetheretherketone and titanium surfaces - Sargon Barkarmo; Daniel Longhorn; Kiran Leer; Carina B. Johansson; Victoria Stenport; Sebastian Franco‐Tabares; Sarah A. Kuehne; Rachel Sammons (Wiley, 2019)
Abstract Objective Polyetheretherketone (PEEK) is a polymer used in devices in orthopedic and dental rehabilitation. The aim of this in vitro study was to compare biofilm formation by a range of important oral bacterial species on PEEK, blasted PEEK, commercially pure titanium (cp‐Ti), and titanium‐6 aluminium‐4 vanadium (Ti6Al4V). Material and methods Coin‐shaped samples were manufactured, and the surfaces were characterized using optical interferometry, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and contact angle measurements. Bacterial species of Streptococcus sanguinis, Streptococcus oralis, Enterococcus faecalis, and Streptococcus gordonii were cultured on the four material surfaces for varying amounts of time. Biofilms were quantified following staining with crystal violet. Results Roughness and contact angle results showed blasted PEEK > PEEK > cp‐Ti = Ti6Al4V. There was increased biofilm formation on blasted PEEK by S. sanguinis, S. oralis, and S. gordonii, whereas the bacterial adhesion was similar on PEEK, cp‐Ti, and Ti6Al4V. The bacterial growth of E. faecalis was significantly higher on cp‐Ti compared with the other three groups. Conclusion The results, taking into consideration the biofilm formation, suggest that PEEK should perform as well as cp‐Ti or TiAl6V4 when used as a dental restorative material.